The Impact of Urban Trees on Air Pollution in Kirkuk City: A Gaussian Dispersion Model Approach - Ahmed Saeed Salih; Nihad Davut Hassan (NTU Journal of Engineering and Technology)
The city of Kirkuk is facing a real crisis in increasing air pollution due to the oil facilities and the lack of trees and their uneven distribution, which exacerbated the problem. This study aims to demonstrate the effect (size, type, and distribution) of urban trees on air pollution in Kirkuk, with a focus on simulating the dispersion of pollutants resulting from the oil refinery. using the Gaussian dispersion model. We will assess the role of existing trees in reducing pollution and explore the potential benefits of planting new trees and their role in reducing air pollution. The study's results inform urban tree’s role in reducing air pollution and strategies for integrating them into city planning. The Gaussian model adds scientific rigor, accurately simulating and evaluating pollution distribution. This methodology serves as a strong basis for analyzing tree effects on air pollution in Kirkuk and other urban areas, aiding evidence-based decision-making to improve air quality and public health.